Quantifying pH-induced changes in plasma strong ion difference during experimental acidosis: clinical implications for base excess interpretation - Giosa, Lorenzo; Zadek, Francesco; Busana, Mattia; De Simone, Giovanna; Brusatori, Serena; Krbec, Martin; Duska, Frantisek; Brambilla, Paolo; Zanella, Alberto; Di Masi, Alessandra; Caironi, Pietro; Perez, Emanuele; et al. (Journal of applied physiology (1985), 2024)
It is commonly assumed that changes in plasma strong ion difference (SID) result in equal changes in whole blood base excess (BE). However, at varying pH, albumin ionic-binding and transerythrocyte shifts alter the SID of plasma without affecting that of whole blood (SIDwb), i.e., the BE. We hypothesize that, during acidosis, 1) an expected plasma SID (SIDexp) reflecting electrolytes redistribution can be predicted from albumin and hemoglobin's charges, and 2) only deviations in SID from SIDexp reflect changes in SIDwb, and therefore, BE. We equilibrated whole blood of 18 healthy subjects (albumin = 4.8 ± 0.2 g/dL, hemoglobin = 14.2 ± 0.9 g/dL), 18 septic patients with hypoalbuminemia and anemia (albumin = 3.1 ± 0.5 g/dL, hemoglobin = 10.4 ± 0.8 g/dL), and 10 healthy subjects after in vitro-induced isolated anemia (albumin = 5.0 ± 0.2 g/dL, hemoglobin = 7.0 ± 0.9 g/dL) with varying CO2 concentrations (2-20%). Plasma SID increased by 12.7 ± 2.1, 9.3 ± 1.7, and 7.8 ± 1.6 mEq/L, respectively (P < 0.01) and its agreement (bias[limits of agreement]) with SIDexp was strong: 0.5[-1.9; 2.8], 0.9[-0.9; 2.6], and 0.3[-1.4; 2.1] mEq/L, respectively. Separately, we added 7.5 or 15 mEq/L of lactic or hydrochloric acid to whole blood of 10 healthy subjects obtaining BE of -6.6 ± 1.7, -13.4 ± 2.2, -6.8 ± 1.8, and -13.6 ± 2.1 mEq/L, respectively. The agreement between ΔBE and ΔSID was weak (2.6[-1.1; 6.3] mEq/L), worsening with varying CO2 (2-20%): 6.3[-2.7; 15.2] mEq/L. Conversely, ΔSIDwb (the deviation of SID from SIDexp) agreed strongly with ΔBE at both constant and varying CO2: -0.1[-2.0; 1.7], and -0.5[-2.4; 1.5] mEq/L, respectively. We conclude that BE reflects only changes in plasma SID that are not expected from electrolytes redistribution, the latter being predictable from albumin and hemoglobin's charges.NEW & NOTEWORTHY This paper challenges the assumed equivalence between changes in plasma strong ion difference (SID) and whole blood base excess (BE) during in vitro acidosis. We highlight that redistribution of strong ions, in the form of albumin ionic-binding and transerythrocyte shifts, alters SID without affecting BE. We demonstrate that these expected SID alterations are predictable from albumin and hemoglobin's charges, or from the noncarbonic whole blood buffer value, allowing a better interpretation of SID and BE during in vitro acidosis.
Keywords: Anemia; Hydrogen-Ion Concentration; poruchy acidobazické rovnováhy; Acidosis; elektrolyty; lidé; Albumins; Acid-Base Imbalance; Carbon Dioxide; acidóza; Electrolytes; albuminy; Hemoglobins; oxid uhličitý; Acid-Base Equilibrium; hemoglobiny; anemie; acidobazická rovnováha; koncentrace vodíkových iontů; Humans